98.3k views
2 votes
For
f(x) = 3x + 1 and
g(x) = x^(2) - 6, find
(f * g)(x)

A.
3x^(2) - 17
B.
3x^(3) + x^(2) - 6x -6
C.
4x^(2) -6x - 8
D.
3x^(3) + x^(2) - 18x -6

User James DW
by
4.9k points

1 Answer

4 votes

Answer:


3x^3+x^2-18x-6

Explanation:

f(x)= 3x+1 and g(x)= x^2 - 6

we need to find (f*g)(x)

(f*g)(x)= f(x) * g(x)

Plug in the given f(x) and g(x)


(f*g)(x)= f(x) * g(x)= (3x+1)(x^2-6)

Apply FOIL method to multiply it


(3x+1)(x^2-6)= 3x^3 -18x+x^2-6= 3x^3+x^2-18x-6

User Sherwin Flight
by
4.8k points